Big endothelin changes the cellular miRNA environment in TMOb osteoblasts and increases mineralization. (August 2014) - Johnson, Michael G.; Kristianto, Jasmin; Yuan, Baozhi; Konicke, Kathryn; Blank, Robert
Abstract Introduction: Endothelin (ET1) promotes the growth of osteoblastic breast and prostate cancer metastases. Conversion of big ET1 to mature ET1, catalyzed primarily by endothelin converting enzyme 1 (ECE1), is necessary for ET1's biological activity. We previously identified the Ece1, locus as a positional candidate gene for a pleiotropic quantitative trait locus affecting femoral size, shape, mineralization, and biomechanical performance. Methods: We exposed TMOb osteoblasts continuously to 25 ng/ml big ET1. Cells were grown for 6 days in growth medium and then switched to mineralization medium for an additional 15 days with or without big ET1, by which time the TMOb cells form mineralized nodules. We quantified mineralization by alizarin red staining and analyzed levels of miRNAs known to affect osteogenesis. Micro RNA 126-3p was identified by search as a potential regulator of sclerostin (SOST) translation. Results: TMOb cells exposed to big ET1 showed greater mineralization than control cells. Big ET1 repressed miRNAs targeting transcripts of osteogenic proteins. Big ET1 increased expression of miRNAs that target transcripts of proteins that inhibit osteogenesis. Big ET1 increased expression of 126-3p 121-fold versus control. To begin to assess the effect of big ET1 on SOST production we analyzed both SOST transcription and protein production with and without the presence of big ET1 demonstrating that transcription and translation were uncoupled Conclusion: Our data show that big ET1 signaling promotes mineralization. Moreover, the results suggest that big ET1's osteogenic effects are potentially mediated through changes in miRNA expression, a previously unrecognized big ET1 osteogenic mechanism.